A Prospective Non-Randomised Interventional Study of Goal-Directed Ultrafiltration Compared With Clinical Dry-Weight Assessment in Achieving Euvolemic Status of Patients on Maintenance Hemodialysis - Pankaj Ganvir; Choudhury Sudhiranjan Dash; Amjad Khan Pathan; Rushi Deshpande; Ashay Shingare; Madan Mohan Bahadur; Ashwin Patil (Journal of Renal and Hepatic Disorders, 2023)
An accurate assessment of intravascular volume status in hemodialysis (HD) patients presents a significant challenge. Current clinical practices to determine dry weight is flawed due to interobserver variability and nonreproducibility. This miscalculation results in either chronic hypervolemia or hypovolemia with intra or interdialytic hypotension. The quest for noninvasive volume assessment tools to aid in the estimation of dry weight still continues. This study aims at goal-directed ultrafiltration removal compared with clinical dry-weight assessment in achieving euvolemic status of patients on chronic HD. It is a prospective, single-centered, nonrandomized, noninvasive interventional study on HD patients, for 12 months. Fifty two patients participated out of which 46 completed the study. Ultrasound-guided inferior vena cava collapsing index (IVCCI) and B lines were measured at intervals along with cardiac parameters. Dry weight was first estimated clinically by trial and error method. New dry weight target was set when B-lines were less than four in the eight site lung ultrasound and IVCCI between 50 and 75%, after 30 min post dialysis. Approximately 23.9% of the patients did not require dry-weight modification throughout the study. About 19% patients did not achieve dry weight in spite of all interventions. Overall, 56.5% of the patients achieved dry weight during the study period. A total of 46.3% of patients with NYHA Grade 3 dyspnoea observed at the start of study was reduced to 2.2%, showing statistical significance. Clinical assessment when bundled with noninvasive technology of assessment of dry weight showed encouraging results. B-lines and IVCCI estimation could be additional tools to achieve target weight goals, reducing complications and increasing compliance.